Comparative analysis, distribution, and characterization of microsatellites in Orf virus genome - Basanta Pravas Sahu (Nature Portfolio, 2020)
Abstract Genome-wide in-silico identification of microsatellites or simple sequence repeats (SSRs) in the Orf virus (ORFV), the causative agent of contagious ecthyma has been carried out to investigate the type, distribution and its potential role in the genome evolution. We have investigated eleven ORFV strains, which resulted in the presence of 1,036–1,181 microsatellites per strain. The further screening revealed the presence of 83–107 compound SSRs (cSSRs) per genome. Our analysis indicates the dinucleotide (76.9%) repeats to be the most abundant, followed by trinucleotide (17.7%), mononucleotide (4.9%), tetranucleotide (0.4%) and hexanucleotide (0.2%) repeats. The Relative Abundance (RA) and Relative Density (RD) of these SSRs varied between 7.6–8.4 and 53.0–59.5 bp/kb, respectively. While in the case of cSSRs, the RA and RD ranged from 0.6–0.8 and 12.1–17.0 bp/kb, respectively. Regression analysis of all parameters like the incident of SSRs, RA, and RD significantly correlated with the GC content. But in a case of genome size, except incident SSRs, all other parameters were non-significantly correlated. Nearly all cSSRs were composed of two microsatellites, which showed no biasedness to a particular motif. Motif duplication pattern, such as, (C)-x-(C), (TG)-x-(TG), (AT)-x-(AT), (TC)- x-(TC) and self-complementary motifs, such as (GC)-x-(CG), (TC)-x-(AG), (GT)-x-(CA) and (TC)-x-(AG) were observed in the cSSRs. Finally, in-silico polymorphism was assessed, followed by in-vitro validation using PCR analysis and sequencing. The thirteen polymorphic SSR markers developed in this study were further characterized by mapping with the sequence present in the database. The results of the present study indicate that these SSRs could be a useful tool for identification, analysis of genetic diversity, and understanding the evolutionary status of the virus.